The efficacy and safety of intravesical chondroitin sulphate solution in recurrent urinary tract infections - M. S. Rahnama’i; A. Javan Balegh Marand; K. Röschmann-Doose; L. Steffens; H. J. Arendsen (BMC Urology, 2022)
Abstract Background Urinary tract infections are among the most common indications for antibiotic therapy. The emergence of resistant uropathogens indicates the need for treatment alternatives. Replenishment of the glycosaminoglycan layer of the bladder, achieved by intravesical instillation of e.g. chondroitin sulphate (CS), is described to be a cornerstone in the therapy of cystitis. To retrospectively evaluate the efficacy of a therapy with 0.2% CS in patients suffering recurrent urinary tract infections (rUTI) in comparison to a treatment with low-dose long-term antibiotics (LDLTAB) and a combination of both. Methods A total of 151 patients with recurrent UTI who underwent intravesical therapy at Diaconesse hospital in Leiden, The Netherlands were included. 50 patients had been treated with CS, 51 patients had received LDLTAB, and 50 patients had received a combination therapy (LDLTABCS). Data recorded for baseline, after 6, and 12 months of treatment were evaluated. Descriptive statistics were calculated. Exploratory comparisons between groups and within groups were performed by using one-tailed and paired t-tests. Patients filled in a standardized quality of life questionnaire (EQ-5D). Results We found a statistically significant reduction of number of infections from 7.10 ± 0.50 SEM to 0.45 ± 0.07 SEM after 12 months therapy with CS compared to 12 months therapy with LDLTAB (from 7.04 ± 0.47 SEM to 1.8 ± 0.15 SEM). The number of visits to the urologist significantly decreased in the CS group from 7.46 ± 0.80 SEM to 1.28 ± 0.11 SEM and from 4.10 ± 0.29 SEM to 1.35 ± 0.11 SEM in the LDLTABCS group. In addition, a significant increase in Quality of life (QoL) was seen in the CS-group (from 58.2 ± 0.82 SEM to 80.43 ± 0.82 SEM) and in the LDLTABCS group (from 62.4 ± 0.97 SEM to 76.73 ± 1.06 SEM). There was no improvement in QoL with LDLTAB (from 58.24 ± 1.08 SEM to 58.96 ± 1.19 SEM). Evaluation’s evidence is limited due to its retrospective character. Conclusions Retrospective analysis of data from patients that underwent therapy for rUTIs confirms the safety and efficacy of CS and indicate a superiority to antibiotic treatment of rUTIs.